2013
DOI: 10.1109/tase.2013.2253769
|View full text |Cite
|
Sign up to set email alerts
|

Automated Identification of Plywood Using Embedded Inkjet-Printed Passive UHF RFID Tags

Abstract: The use of passive ultra high-frequency (UHF) radio frequency identification (RFID) integrated into plywood boards is proposed to enable the identification and tracking of individual plywood boards and end products of plywood. For the first time, tags are embeddable inside plywood by direct inkjet-printing tag antennas on pure birch veneer. The use of passive UHF RFID technology in the applications of plywood industry is discussed, two tag antenna designs for plywood are presented and the tag fabrication proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…In the direction of the grain, such variations are low, whereas against the grain, variations are significant. In fact, in our previous study, it was found that RFID tag antennas inkjet-printed on wood veneer only in one direction did not function even with several layers of conductive ink, and that antennas that had the antenna geometry printed along the grain showed the best performance [3]. This was also discovered in our preliminary tests; the conductivity of the antenna brushed against the grain was significantly lower than conductivity of the antenna brushed along the grain.…”
Section: Fabrication Of the Sample Tags On Wood Substratesupporting
confidence: 61%
See 4 more Smart Citations
“…In the direction of the grain, such variations are low, whereas against the grain, variations are significant. In fact, in our previous study, it was found that RFID tag antennas inkjet-printed on wood veneer only in one direction did not function even with several layers of conductive ink, and that antennas that had the antenna geometry printed along the grain showed the best performance [3]. This was also discovered in our preliminary tests; the conductivity of the antenna brushed against the grain was significantly lower than conductivity of the antenna brushed along the grain.…”
Section: Fabrication Of the Sample Tags On Wood Substratesupporting
confidence: 61%
“…In our previous study, inkjet-printed and heat-sintered silver nanoparticle UHF RFID tags on wood veneer, with quite similar tag antenna geometry, achieved peak read ranges of 6.5 m and read ranges of over 2 m throughout the global UHF RFID band [3]. Thus, these brush-painted antennas offer an alternative to inkjet-printed antennas on wood substrates.…”
Section: Evaluation Of the Rfid Tag Performancementioning
confidence: 82%
See 3 more Smart Citations